Positive Politeness Strategies Used by Characters in an Animation Movie Script Entitled “Finding Dory” - Darma Putra, Gede; Parthama, I Gusti Ngurah (Humanis; Vol 22 No 4 (2018)DO - 10.24843/JH.2018.v22.i04.p02, 2018)
The title of this study is Positive Politeness Strategies Used by Characters in an Animation Movie entitled “Finding Dory”. This study is aimed at finding out the types of positive politeness strategies used to extend and respond by the characters to express the utterance in movie script and also what factors that influence the usage of positive politeness strategies in the “Finding Dory” movie. The analysis of this study is concerned with the utterance of positive politeness strategies of the characters. The data of this study were collected through conducting direct observation of the movie script “Finding Dory” produced by Pixar Animation Studios and directed by Andrew Stanton (2016). The collected data then were identified, classified, and analyzed qualitatively. The data derived from the script of the “Finding Dory” movie were collected and then, analyzed the polite expressions of characters used while doing conversation. After that, the selected data were analyzed based on the theory of politeness proposed by Brown and Levinson. Based on the result of the analysis, it was found that when extending and responding the utterance that contains positive politeness strategies, the characters used intensify interest to H (3),  in-group identity markers (4), presuppose/raise/assert common ground (7), assert or presuppose S's knowledge of and concern for H's wants (9), offer, promise (10), be optimistic (11), including both S and H in the activity (12), give (or ask for) reasons (sub-strategy 13), assume or assert reciprocity (14). The most prominent factor that influences the characters to extend and respond the positive politeness strategies is the circumstances: sociological variables.